Information and Communication Technologies in Tourism 2021 2021
DOI: 10.1007/978-3-030-65785-7_24
|View full text |Cite
|
Sign up to set email alerts
|

Cultural Traits in the Consumption of Luxury Hotel Services

Abstract: This study investigates luxury hotel guests’ online reviews to explore how ratings, language and sentiment differ according to guests’ culture of origin. The study considers three large cultural groups (Asian, North American, and European) examining hotel guests in their reviews to identify the most recurring themes in association with luxury tourism.The study uses automated text analysis to explore 16,415 hotel reviews from 22 luxury hotel brands belonging to nine global hotel chains located across six Europe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 43 publications
1
5
0
Order By: Relevance
“…Among the peer-reviewed article that cited this is Platania et al (2019) who examined tourist behavior in luxury hotels. This study affirms both the tangible and intangible components of luxury (D’Acunto and Volo, 2021) and call for further research in the field of luxury travel to contribute to the further understanding of luxury travel. It is also implied that there is a further need to test this framework in the context of post-pandemic tourism where tourists’ behavior is uncertain (Uğur and Akbıyık, 2020).…”
Section: Hierarchy Of Luxury Travel Needssupporting
confidence: 76%
See 1 more Smart Citation
“…Among the peer-reviewed article that cited this is Platania et al (2019) who examined tourist behavior in luxury hotels. This study affirms both the tangible and intangible components of luxury (D’Acunto and Volo, 2021) and call for further research in the field of luxury travel to contribute to the further understanding of luxury travel. It is also implied that there is a further need to test this framework in the context of post-pandemic tourism where tourists’ behavior is uncertain (Uğur and Akbıyık, 2020).…”
Section: Hierarchy Of Luxury Travel Needssupporting
confidence: 76%
“…The idea of luxury is usually associated with expensive products and services where only those with greater disposable income can afford. This was affirmed by D’Acunto and Volo (2021), who revealed that physical attributes dominate the guests’ perception of luxury. This study further revealed that, when the geographical origins of tourists are considered, a deeper view of luxury can be seen, where service, location and stay impact perceptions.…”
Section: Luxury Travelmentioning
confidence: 92%
“…First, although we considered a diverse set of destinations and properties, our relatively small sample of luxury hotels could temper results’ generalizability. Moreover, research suggests that culture can influence customers’ evaluations of luxury hotel experiences (D’Acunto & Volo, 2021). Our work should therefore be expanded to a larger scale in the future.…”
Section: Limitations and Future Researchmentioning
confidence: 99%
“…Recent literature has explored cultural traits and related behavioral differences in OTRs by investigating language as a discriminating cultural factor (Liu et al, 2017), macro-areas of residence and cultural backgrounds (Ayeh et al, 2016;D'Acunto and Volo, 2021;Galati and Galati, 2019;Mariani and Predvoditeleva, 2019). A few studies have focused on hotel reviews and restaurant experiences, showing a growing interest in the use of OTRs to explore cultural traits and related behavioral differences (Jia, 2020;Nakayama and Wan, 2018).…”
Section: Literature Reviewmentioning
confidence: 99%